Respiratory health impact of haze exposure and its financial implications / Mohd Hafiz Jaafar - Mohd Hafiz, Jaafar (2019)
Haze imposes a substantial disease burden on populations, especially those in the Southeast Asian region. In Malaysia, haze episodes have been primarily associated with transboundary sources following biomass burning of peat, soil and forests in neighbouring countries. Local anthropogenic sources, especially from domestic waste burning, motor vehicle emissions and industrial production, also contributed significantly to the occurrence of haze episodes in this rapidly developing country. It is important to determine the trends in haze episodes and in associated healthcare utilisation and healthcare costs, particularly for respiratory illnesses. This study aimed to describe the haze situation and factors associated with haze episodes in Selangor. It also sought to determine healthcare utilisation and healthcare costs incurred by public healthcare providers. A cross-sectional study was conducted using secondary data from 2012 to 2015 on air pollutants and ecological factors obtained from the Department of Environment and healthcare utilisation data retrieved from the Ministry of Health Malaysia and the University Malaya Medical Centre. The calculation of costs associated with managing haze-related respiratory illnesses was based on the unit cost derived from other studies. This was used to compare the direct medical cost for treatment of haze-related respiratory illnesses during haze and non-haze episodes. In this study, haze episodes were defined based on average monthly PM10 readings. Between 2012 and 2015, a total of 129 (67.2%) haze episodes were recorded at four selected stations in Selangor. The haze episodes were associated with higher healthcare utilisation due to haze-related respiratory illnesses in general and for both inpatient and outpatient visits (p<0.05). The numbers of inpatient and outpatient visits during haze episodes were 74 iv (± 62.1) and 320 (± 650.1), respectively, compared to 34 (± 16.5) and 146 (± 170.5), respectively, during non-haze episodes. The four-year cumulative direct medical cost differences between haze and non-haze episodes were RM 13.4 million for inpatient cases and RM1.4 million for outpatient cases. The total cost difference during haze and non-haze episodes was approximately RM14.9 million. Findings showed that more haze episodes than non-haze episodes were recorded between 2012 and 2015 in Selangor. The deterioration in air quality due to haze episodes creates a significant financial burden for the public healthcare system as the result of increased utilisation. It is essential to implement a mitigation policy and to educate the population in order to reduce exposure to haze and to ensure that adequate financial and human resources are available in the relevant healthcare facilities to minimise the health and financial impacts of haze.